ASSESSMENT OF PASSIVE SMOKING EXPOSURE AMONG PREGNANT WOMEN - ARIF , ZSK; BEGUM , R; TASNEEM , SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Secondhand smoke (SHS) exposure poses significant health risks to both mothers and fetuses during pregnancy. Despite global efforts to reduce smoking in public and private spaces, SHS exposure remains prevalent, particularly in low- and middle-income countries. Objective: The study aimed to assess the extent of passive smoking exposure among pregnant women in various settings, including their homes, workplaces, and public spaces, and to examine the frequency and potential health risks associated with SHS exposure during pregnancy. Methods: This cross-sectional study was conducted among 150 pregnant women attending a tertiary care hospital in Pakistan between January and June 2024. Data were collected using a structured questionnaire that captured demographic information and SHS exposure across different environments, including home, workplace, and public spaces. Descriptive statistics, including frequencies and percentages, were used to summarize the data. Results: Among the participants, 60.7% reported SHS exposure at home, with 30% experiencing SHS exposure 6-10 times weekly. Additionally, 61.3% of the women reported exposure at work, with 52.7% exposed 11-15 times monthly. Public spaces also contributed to significant SHS exposure, with 86% of participants affected. Notably, 37.3% of women reported spending 15-30 minutes daily inside a car with someone smoking. Demographically, most participants were aged 25-28 years (46.7%) and had a matric-level education (36.0%). Conclusion: This study reveals a high prevalence of SHS exposure among pregnant women, particularly at home, work, and public places. The findings underscore the urgent need for public health interventions, such as stricter smoke-free policies and public awareness campaigns, to reduce SHS exposure and safeguard maternal and fetal health.